Biomechanical characteristics of mogul skiing turn - Riku, V.; Miettunen, K. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: In mogul skiing 50% of final points of a competition run are based on the points given by judges related to turning technique. The remainder of the points comes from run time (25%) and Jumps (25%). Thus, appropriate turning technique combined with fast running time are very important factors for success in mogul skiing. The purpose of this study was to determine angular changes of knee joint and EMG-activity during the mogul skiing turns among top-level freestyle skiers.